Predicting extended operative time and length of inpatient stay in cervical deformity corrective surgery. (November 2019) - Horn, Samantha R.; Passias, Peter G.; Bortz, Cole A.; Pierce, Katherine E.; Lafage, Virginie; Lafage, Renaud; Brown, Avery E.; Alas, Haddy; Smith, Justin S; Line, Breton; Deviren, Vedat; Mundis, Gregory M.; et al.
Highlights: Identification of predictors of extended op-time and length of stay in CD patients. Levels fused, surgical approach, BMI and osteotomy predicted op-time and LOS. Baseline cSVA and C0 slope predicted increased LOS and op-time. Patient care, hospital efficiency, and resource allocation can be optimized. Abstract: It's increasingly common for surgeons to operate on more challenging cases and higher risk patients, resulting in longer op-time and inpatient LOS. Factors predicting extended op-time and LOS for cervical deformity (CD) patients are understudied. This study identified predictors of extended op-time and length of stay (LOS) after CD-corrective surgery. CD patients with baseline (BL) radiographic data were included. Patients were stratified by extended LOS (ELOS; >75th percentile) and normal LOS (N-LOS; <75th percentile). Op-time analysis excluded staged cases, cases >12 h. A Conditional Variable Importance Table used non-replacement sampling set of Conditional Inference trees to identify influential factors. Mean comparison tests compared LOS and op-time for top factors. 142 surgical CD patients (61 yrs, 62%F, 8.2 levels fused). Op-time and LOS were 358 min and 7.2 days; 30% of patients experienced E-LOS (14 ± 13 days). Overlapping predictors of E-LOS and op-time included levels fused (>7 increased LOS 2.7 days; >5 increased op-time 96 min, P < 0.001), approach (anterior reduced LOS 3.0 days; combined increased op-time 69 min, P < 0.01), BMI (>38 kg/m 2 increased LOS 8.1 days; >39 kg/m 2 increased op-time 17 min), and osteotomy (LOS 2.0 days, op-time 62 min, P < 0.005). BL cervical parameters increased LOS and op-time: cSVA (>42 mm increased LOS; >50 mm increased op-time, P < 0.030), C0 slope (>@−0.9° increased LOS, >0.3° increased op-time, P < 0.003.) Additional op-time predictors: prior cervical surgery (p = 0.004) and comorbidities (P = 0.015). Other predictors of E-LOS: EBL (P < 0.001), change in mental status (P = 0.001). Baseline cervical malalignment, levels fused, and osteotomy predicted both increased op-time and LOS. These results can be used to better optimize patient care, hospital efficiency, and resource allocation.